Static voltage stability margin evaluation for a DC distribution network with DC electric springs - Xiaolong Xu; Qianggang Wang; Jianquan Liao; Yuan Chi; Tao Huang; Niancheng Zhou; Yiyao Zhou; Xuefei Zhang (International Journal of Electrical Power & Energy Systems)
The rapid growth of DC loads in distribution networks positions DC distribution networks as a promising solution for future power systems. However, the operational limits of power electronic devices in DC distribution networks may pose static voltage stability challenges. Accurate evaluation of the static voltage stability margin is crucial to prevent such issues. As a flexible resource, the DC electric spring would significantly impact the static voltage stability margin of a DC distribution network. This paper proposes a static voltage stability margin evaluation method for DC distribution networks with DC electric springs, based on continuation power flow. Initially, the relationship between the outputs of a DC electric spring and load power is analyzed in a simplified circuit, leading to the derivation of bus type conversion logic for buses with DC electric springs, considering their output limits. Using this logic, the proposed method determines the bus type by evaluating the outputs of DC electric springs, identifies any violations, and subsequently applies corrections to the Jacobian matrix. The evaluation also accounts for the current limits of power supply converters. The time-domain simulation results show high consistency with the proposed method, especially in calculating the load power that drives the device outputs to their limits, thereby validating the effectiveness of the approach.